2022
DOI: 10.4102/sajhrm.v20i0.1957
|View full text |Cite
|
Sign up to set email alerts
|

Distinct leadership styles and differential effectiveness across culture: An analysis of South African business leaders

Abstract: Orientation: While some deem business leadership practices as universal, others judge them to be specific to a cultural context, arguing that certain leadership styles are specific to, for example, those from an African or a Western cultural background.Research purpose: The goal of the research was to assess whether the leadership styles of South African leaders differ based on cultural background and whether the effectiveness of these leadership styles is judged differently by subordinates.Motivation for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…While an effective leader can establish a healthy and successful workplace, being an effective leader takes a certain combination of skills and leadership traits that develop over time Carson, 2011;Sun, Chen & Zhang, 2017;Lerutla & Steyn, 2022). Leadership effectiveness is predicated upon a strong balance of interpersonal and intrapersonal skills.…”
Section: Attributes Of Effective Leadersmentioning
confidence: 99%
See 2 more Smart Citations
“…While an effective leader can establish a healthy and successful workplace, being an effective leader takes a certain combination of skills and leadership traits that develop over time Carson, 2011;Sun, Chen & Zhang, 2017;Lerutla & Steyn, 2022). Leadership effectiveness is predicated upon a strong balance of interpersonal and intrapersonal skills.…”
Section: Attributes Of Effective Leadersmentioning
confidence: 99%
“…According to Lowder (2007), certain leadership styles and behaviours result in specific organisational outcomes, and therefore leadership and organisational performance are in a highly correlated cause-and-effect relationship. Leadership effectiveness has been linked to a leader's need for powersuch leaders have a high level of leadership motivation and a strong desire to guide and influence others (Josef & Helena, 2022); emotional and cultural intelligence (Edelman & Knippenberg, 2018;Lerutla & Steyn, 2022) and leadership styles Baig et al, 2021;Ramchunder & Martins, 2014;Solomon & Steyn, 2017). A review of the literature on the qualities of effective leaders revealed that these can be classified into the five categories of attributes as displayed in table 1 below.…”
Section: Attributes Of Effective Leadersmentioning
confidence: 99%
See 1 more Smart Citation
“…The treatment of employees by their leaders is influenced by their leadership style and the cordiality between the leader and his employees (Lee and Farh, 2019). Leaders will unintentionally treat employees within their vicinity differently because of the differential cordiality of relationships; then they try their best to find a balance between "differentiation" and "prioritization" (Lerutla and Steyn, 2022). We not only examine the impact of differential leadership on employee performance but also revise strategies for balancing the differences between coworkers.…”
Section: Introductionmentioning
confidence: 99%
“…While education systems are the backbone of the leadership development pipeline in Africa, less than 1% of those who enter the system get a leadership education (Igué, 2010). The select few who are taught leadership in tertiary institutions learn it from western perspectives that encounter historic, contextual and cultural adaptation challenges that clash with local ethics, values, virtues and community belief systems (Lerutla & Steyn, 2022).…”
Section: Introductionmentioning
confidence: 99%